Management of Educational Institutions in Libya: Integrating Islamic Education with Environmental Responsibility: Manajemen Lembaga Pendidikan di Libya: Mengintegrasikan Pendidikan Islam dengan Tanggung Jawab Lingkungan - Mowafg Masuwd; Shofa Aulia Kumala; Fitroh Khasanah Khasanah (Mapendis: Jurnal Manajemen Pendidikan Islam, 2025)
Libya faces significant environmental challenges such as water scarcity, desertification, and waste management, which impact the sustainability of its ecosystems and the lives of its people. Islamic education has great potential to support environmental sustainability through the integration of ecological principles embodied in the Qur'an. This article aims to explore how educational institutions in Libya can integrate Islamic-based sustainability principles into their curricula. This research uses a qualitative approach with a case study method, collecting data through in-depth interviews with educators and educational institution administrators, and analyzing curriculum documents from various Islamic educational institutions in Libya. The results indicate that while there is great potential to integrate Islamic-based environmental education, the main challenges lie in the lack of government policy support, limited resources, and political instability affecting the education system. This article concludes that realizing sustainability-based education requires more comprehensive educational policy reform and increased collaboration between educational institutions, the government, and the community. This research also recommends developing training for educators to integrate sustainability principles into their teaching.